The Coral Probiotics Village: An Underwater Laboratory to Tackle the Coral Reefs Crisis - Neus Garcias‐Bonet; Helena Villela; Francisca C. García; Gustavo A. S. Duarte; Nathalia Delgadillo‐Ordoñez; Inês Raimundo; Yusuf C. El‐Khaled; Erika P. Santoro; Morgan Bennett‐Smith; Brian O. Nieuwenhuis; João Curdia; Brian Zgliczynski; et al. (Ecology and Evolution, 2025)
ABSTRACT Restoration efforts are urgently needed for the conservation of coral reefs. Among emerging tools, the use of probiotics has shown promise in laboratory settings for improving coral resilience, but their validation under real‐world reef conditions remains limited. Here, we present the Coral Probiotics Village (CPV) as a novel and fully operational underwater research laboratory and a testing ground designed to support the in situ testing of microbial‐based coral restoration interventions. This manuscript describes the design, establishment, and scientific validation of the CPV, including continuous environmental monitoring, a summary of previously developed pilot trials of probiotic applications, and an integration of sensor networks, AI‐assisted reef monitoring, and autonomous technologies. We propose the CPV as a scalable model for integrated coral restoration science and suggest its replication as a tool to accelerate applied reef conservation efforts globally.